Study of visco-elastic-plastic properties of thermoplastic polymers. An integrated experimental and theoretical approach - Garishin, Oleg Konstantinovich; Korlyakov, Anton Sergeevich; Shadrin, Vladimir Vasilievich (Computational Continuum Mechanics, 2014)
The paper describes an integrated experimental and theoretical approach to the study of complex mechanical behavior of thermoplastic polymers under finite deformations. It includes a special experimental technique that allows us to obtain during a single test the necessary data on viscoelastic and elastoplastic polymer properties, as well as a phenomenological differential type model designed for decoding and simulating experimental results. The experimental program consists of the cyclic deformation of sample and includes: stretching - stress relaxation - reducing strain to some predetermined constant value of tensile strength - stress relaxation - next cycle of loading. Each subsequent cycle is performed with increasing strain amplitude. The phenomenological model is based on a differential approach to the construction of constitutive equations of the mechanical behavior of materials with the help of symbolic schemes. This approach uses the mathematical apparatus of mechanics of nonlinear finite deformations involving Runge-Kutta computing method and Nelder-Mead simplex method. The symbolic model scheme consists of two parallel branches containing two serially connected elements: a) elastic and plastic, b) elastic and viscous. The elastoplastic branch represents the behavior of agglomerates of more rigid crystallites, their displacement and destruction during deformation. The viscoelastic branch describes the flow of the amorphous polymer phase. The experimental data obtained for polyethylene PE 107-02K were theoretically analyzed using this model. Dependencies of elastic, plastic and viscous model parameters on polymer deformation were obtained. A comparison of the calculated and experimental results shows high coincidence, which is indicative of the fact that the conclusions drawn from the analysis of the model parameters are close to reality.
Keywords: thermoplastic materials; polyolefines; finite deformations; elastoplasticity; viscoelasticity; symbolic schemes; Runge-Kutta method; Nelder-Mead simplex method